(untitled) (International Journal of Gender, Science and Technology, 2018)
This paper focuses on gender and network awareness and their importance for academic leadership positions in Science, Engineering and Technology (SET). Empirical material stems from a German study (2009 to 2012) which focussed on the potential for innovation among women in leadership positions and the barriers they experience. The basis is a qualitative study with case studies in different organisations, a technical university and different research institutes from one big governmental research organisation. Semi-structured interviews and focus group discussions with female and male professors are the empirical basis for results. Research questions focus on effects of gender awareness on women professors’ strategic responses, different responses of individuals to inequalities when they become more network aware, and the importance of both gender and network awareness to counter inequalities. Gender aware female professors are more successful in individual coping strategies (handling visibility, fighting for acceptance and against discrimination, solidarity and support of women). Gender aware organisational cultures are evident in mentoring programs and equal opportunity policies. Interviewed professors show an overall high networking awareness. They are convinced that successful leadership in a technical field requires inclusion in internal and external networks, especially for information, cooperation and projects. Women in SET need to be gender and network aware to overcome hindrances stemming from their limited participation in powerful informal men’s networks.&